Correction: Urtica dioica Agglutinin: A plant protein candidate for inhibition of SARS-COV-2 receptor-binding domain for control of Covid19 Infection. - Fatemeh Sabzian-Molaei; Mohammad Ali Nasiri Khalili; Mohammad Sabzian-Molaei; Hosein Shahsavarani; Alireza Fattah Pour; Ahmad Molaei Rad; Amin Hadi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0268156.].